Efficacy assessment of main functions of drugstore organizations on Perm' drugstores example - Ye. A. Tretiyakova (Бюллетень сибирской медицины)
Aimed at assessing financial result from commercial, production and social functions of drugstores, cost-functional and corre-lation-regressive analysis was performed. Accounts of Perm' drugstores were the object of the study. Mean profitability of trade function was established to be 13.1%, profitability of social function to be 4.3%, unprofitableness of production function to be 38.8%.